Utilising green and bluespace to mitigate urban heat island intensity - Gunawardena, K.R.; Wells, M.J.; Kershaw, T. (The Science of the total environment, 2017)
It has long been recognised that cities exhibit their own microclimate and are typically warmer than the surrounding rural areas. This ‘mesoscale’ influence is known as the urban heat island (UHI) effect and results largely from modification of surface properties leading to greater absorption of solar radiation, reduced convective cooling and lower water evaporation rates. Cities typically contain less vegetation and bodies of water than rural areas, and existing green and bluespace is often under threat from increasing population densities. This paper presents a meta-analysis of the key ways in which green and bluespace affect both urban canopy- and boundary-layer temperatures, examined from the perspectives of city-planning, urban climatology and climate science. The analysis suggests that the evapotranspiration-based cooling influence of both green and bluespace is primarily relevant for urban canopy-layer conditions, and that tree-dominated greenspace offers the greatest heat stress relief when it is most needed. However, the magnitude and transport of cooling experienced depends on size, spread, and geometry of greenspaces, with some solitary large parks found to offer minimal boundary-layer cooling. Contribution to cooling at the scale of the urban boundary-layer climate is attributed mainly to greenspace increasing surface roughness and thereby improving convection efficiency rather than evaporation. Although bluespace cooling and transport during the day can be substantial, nocturnal warming is highlighted as likely when conditions are most oppressive. However, when both features are employed together they can offer many synergistic ecosystem benefits including cooling. The ways in which green and bluespace infrastructure is applied in future urban growth strategies, particularly in countries expected to experience rapid urbanisation, warrants greater consideration in urban planning policy to mitigate the adverse effects of the UHI and enhance climate resilience. [Display omitted] •The influence of green and bluespace on urban canopy/boundary-layer temperatures.•Tree-dominated greenspace offers greater heat stress relief when most required.•Badly designed bluespace, may exacerbate heat-stress during oppressive conditions.•Boundary-layer cooling is attributed to greenspace increasing surface roughness.•The influence of geometry and diversity of green/bluespaces requires more research.